1991
DOI: 10.1111/bcpt.1991.69.4.238
|View full text |Cite
|
Sign up to set email alerts
|

On the Inhibition of Glutamic Acid Decarboxylase and γ‐Aminobutyric Acid Transaminase by Sodium Cyanide

Abstract: The effects of sodium cyanide (NaCN) on the gamma-aminobutyric acid metabolizing enzymes glutamic acid decarboxylase (GAD) and gamma-aminobutyric acid transaminase (GABA-T) were studied in vitro. With no pyridoxal-5-phosphate added, GAD was non-competitively inhibited by NaCN, with an IC50 of 280 microM. GAD was also inhibited when exposed to an equimolar amount of NaCN and pyridoxal-5-phosphate. NaCN inhibited GABA-T. The inhibition kinetics suggests that NaCN may react with more than one of the substrates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As neurons have relatively high metabolic rates with little capacity for anaerobic metabolism, cyanide may promote neurotoxic effects through inhibition of cellular respiration. Furthermore, cyanide interferes with several neurotransmitters including γ-aminobutyric acid -GABA (Tursky and Sajter, 1962;Cassel et al, 1991), glutamic acid (Cassel et al, 1991), acetylcholine (Owasoya andIramain, 1980), dopamine (Cassel et al, 1995), excitatory amino acids (McCaslin and Yu, 1992;Gunasekar et al, 1996) and nitric oxide (Gunasekar et al, 1996). Even though thiocyanate increases the affinity of AMPA receptors for glutamate (Spencer, 1999), it probably does not contribute to cyanide neurotoxicity because thiocyanatetreated goats had no lesions in nervous system tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As neurons have relatively high metabolic rates with little capacity for anaerobic metabolism, cyanide may promote neurotoxic effects through inhibition of cellular respiration. Furthermore, cyanide interferes with several neurotransmitters including γ-aminobutyric acid -GABA (Tursky and Sajter, 1962;Cassel et al, 1991), glutamic acid (Cassel et al, 1991), acetylcholine (Owasoya andIramain, 1980), dopamine (Cassel et al, 1995), excitatory amino acids (McCaslin and Yu, 1992;Gunasekar et al, 1996) and nitric oxide (Gunasekar et al, 1996). Even though thiocyanate increases the affinity of AMPA receptors for glutamate (Spencer, 1999), it probably does not contribute to cyanide neurotoxicity because thiocyanatetreated goats had no lesions in nervous system tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that cyanide is a direct inhibitor of several enzymes in addition to cytochrome c oxidase. These include succinic acid dehydrogenase, superoxide dismutase, carbonic anhydrase, glutathione peroxidase, NADPH oxidase, myeloperoxidase, glutamic acid decarboxylase, and gamma‐aminobutyric acid transaminase [ 115 , 116 , 117 , 118 , 119 , 120 ]. In contrast, monoamine oxidase A (but not monoamine oxidase B) activity was reported to increase in response to cyanide [ 121 ].…”
Section: Cyanide As An Inhibitor Of Mitochondrial Respiration and As ...mentioning
confidence: 99%
“…Thiocystine has been also shown to directly interact with cyanide thus generating Cys‐SSH and Cys‐SCN [ 293 , 294 , 295 ]. Both CSE and CBS are PLP‐dependent enzymes and, although cyanide has been shown to directly react with PLP, thus leading to enzyme inhibition [ 118 ], there are no reports suggesting a such reaction in the case of CSE and CBS. The presence of a heme prosthetic group makes the latter enzyme a potential target for small molecule such gasotransmitters, as shown for NO and CO [ 296 ].…”
Section: Multiple Interactions Exist Between Various Gasotransmittersmentioning
confidence: 99%
“…We have previously reported that acute sodium cyanide poisoning decrease the levels of GABA, glutamic acid and glutamine and increase dose-dependent the cerebellar cyclic GMP in the striatum (Persson et al 1985). An inhibition in the synthesis and metabolism of GABA after treatment with sodium cyanide has also been shown by Cassel et al (1991). A decreased GABA activity during cyanide intoxication would in part explain the increased susceptibility to convulsions (Tapia 1975).…”
Section: Discussionmentioning
confidence: 97%